2003
DOI: 10.1079/bjn2003980
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial energy metabolism in a model of undernutrition induced by dexamethasone

Abstract: The present investigation was undertaken to evaluate whether mitochondrial energy metabolism is altered in a model of malnutrition induced by dexamethasone (DEX) treatment (1·5 mg/kg per d for 5 d). The gastrocnemius and liver mitochondria were isolated from DEX-treated, pair-fed (PF) and control (CON) rats. Body weight was reduced significantly more in the DEX-treated group (2 16 %) than in the PF group (2 9 %). DEX treatment increased liver mass (þ 59 % v. PF, þ23 % v. CON) and decreased gastrocnemius mass. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 64 publications
6
23
1
1
Order By: Relevance
“…In particular, reported prolactin effects on liver and white adipose tissue lipogenic gene expression and function are opposite to those observed after ghrelin treatment in the current study (1). In addition, excess glucocorticoids are not reported to exert independent effects on hepatic lipogenesis and lipid deposition (14,29,54), whereas most (16,18,30), although not all (55), reports agree on their suppressive or null effect on skeletal muscle mitochondrial function. Thus, taken together, the above observations do not support a major role of additional hypophyseal hormonal changes in observed metabolic effects.…”
Section: Discussioncontrasting
confidence: 63%
“…In particular, reported prolactin effects on liver and white adipose tissue lipogenic gene expression and function are opposite to those observed after ghrelin treatment in the current study (1). In addition, excess glucocorticoids are not reported to exert independent effects on hepatic lipogenesis and lipid deposition (14,29,54), whereas most (16,18,30), although not all (55), reports agree on their suppressive or null effect on skeletal muscle mitochondrial function. Thus, taken together, the above observations do not support a major role of additional hypophyseal hormonal changes in observed metabolic effects.…”
Section: Discussioncontrasting
confidence: 63%
“…1A, 1B). Moreover, it has been described that dexamethasone-treated muscle cells increase the rate of nonphosphorylative oxygen consumption (31) and that vitamin D 3 increases ROS production (32), which may suggest less efficient ATP production from OXPHOS. Interestingly, tolerogenic moDCs were more affected by etomoxir than oligomycin in terms of ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dexamethasone being a highly reproducible model of hypermetabolic stress [12,13,17], a similar experiment was conducted in a parallel group of rats to test plasma substrate and hormone concentrations. In a third experiment, rats were anaesthetised with isoflurane, the skin over the leg was dissected away and the gastrocnemius was rapidly freeze-clamped, removed, frozen in liquid nitrogen and subsequently stored at −80°C until analysis of PCr and creatine concentration.…”
Section: Animalsmentioning
confidence: 99%
“…GCTC-induced insulin resistance results in decreased insulin-stimulated glucose uptake in muscle [6], and increased plasma concentrations of NEFA, insulin and leptin [7,8], with troglitazone antagonising this effect [7]. At the whole body level, increased GCTC concentrations are known to increase oxygen consumption [9][10][11], and decrease food intake [12,13] resulting in a more negative energy balance than in pair-fed animals. We have shown that there is a decreased efficiency of oxidative phosphorylation in the liver mitochondria of dexamethasone treated rats [13].…”
mentioning
confidence: 99%